Occurrence of Cryptosporidium and other enteropathogens and their association with diarrhea in dairy calves of Buenos Aires province, Argentina - Garro, Carlos Javier (2021)
Cryptosporidiosis of neonatal dairy calves causes diarrhea, resulting in important economic losses. In Argentina, prevalence values of Cryptosporidium spp. and other enteropathogens such as group A rotavirus (RVA), bovine coronavirus (BCoV) and enterotoxigenic Escherichia coli (ETEC, endotoxin STa+), have been independently studied in different regions. However, an integrative epidemiological investigation on large-scale farms has not been carried out. In this study, fecal samples (n = 908) were randomly collected from diarrheic and healthy calves from 42 dairy farms, and analyzed for the presence of Cryptosporidium spp., RVA, BCoV, ETEC (STa+) and Salmonella spp. In all sampled dairy farms, dams had been vaccinated against rotavirus and gram-negative bacteria to protect calves against neonatal diarrhea. The proportion of calves shedding Cryptosporidium spp., RVA, and BCoV in animals younger than 20 days of age were 29.8%, 12.4% and 6.4%, and in calves aged between 21 and 90 days, 5.6%, 3.9%, and 1.8%, respectively. ETEC was absent in the younger, and occurred only sporadically in the older group (0.9%), whereas Salmonella spp. was absent in both. The observed sporadic finding or even absence of bacterial pathogens might be explained by the frequent use of parenteral antibiotics in 25.3% and 6.5% of the younger and the older group of calves, respectively, within 2 days prior to sampling and/or vaccination of dams against gram-negative bacteria. Diarrhea was observed in 28.8% (95% CI, 24.7–32.8%) of the younger calves and 11.7% (95% CI, 9.1–15.5%) of the older calves. Importantly, Cryptosporidium spp. (odds ratio (OR) = 5.7; 95% CI, 3.3–9.9; p < 0.0001) and RVA (OR = 2.5; 95% CI, 1.2–5.1; p < 0.05) were both found to be risk factors for diarrhea in calves younger than 20 days old. Based on its high prevalence and OR, our results strongly suggest that Cryptosporidium spp. is the principal causative factor for diarrhea in the group of neonatal calves, whereas RVA seems to play a secondary role in the etiology of diarrhea in the studied farms, with about three-times lower prevalence and a half as high OR. Furthermore, a coinfection rate of Cryptosporidium spp. and RVA of 3.7% was observed in the group of younger calves, which strengthens the assumption that these events are independent. In contrast, due to a low infection rate of enteropathogens in older calves, mixed infection (<< 1%) was virtually absent in this group.